Cashless Muslim Society Transformation Strategy - Harahap, Ramadhan; Andri Soemitra; Ridwan, Muhammad (LPPM, Universitas Islam Syarifuddin Lumajang, 2025)
This study delves into the strategic transformation of Muslim communities into cashless societies, with a specific focus on the determinants of user acceptance and behavioral influences. Embracing a comprehensive approach, the research thoroughly examines existing literature, unraveling the inherent complexities of this societal shift. Meticulous detailing of key findings captures the factors shaping user acceptance within the context of a theoretical model situated in a broader conceptual framework. The research methodology employs tailored open-ended questions to explore Muslim user acceptance, ensuring meticulous transcription and in-depth analysis of interview data for result reliability. The outcomes highlight dynamics at play, challenging conventional assumptions by underscoring the significance of pull factors in driving acceptance. Implications derived from this research offer actionable insights for practitioners and contribute substantively to the existing literature on Muslim societal transformation. The findings affirm the relevance of the adopted theoretical framework, providing a lens through which to interpret and navigate evolving Muslim consumer behavior in the transition toward cashless societies.